Perception of Patients with Diabetes Comorbidities on Polypharmacy and Deprescribing in a Public Healthcare Setting - Sandrea Alby, Reshma George, Aksa Roy, Y Joel Isaac, Roja B , Someshwaran S, Mohsina Hyder, V. Arun Kumar , V. Jothibasu (South Eastern European Journal of Public Health, 2025)
The primary objective is to determine patients’ and caregivers’ attitude towards polypharmacy and deprescribing by administering a revised Patients’ Attitudes Towards Deprescribing questionnaire. Secondary objective is to identify and compare individual characteristics associated with these attitudes and beliefs, and to perform Treatment Chart Review. A prospective cross-sectional questionnaire based-study was carried out on 250 type 2 diabetes patients with comorbidities visiting public health care setting within the Nilgiris for a period of 6 months. Patient’s comorbid conditions and concurrent medication were analysed, and a Treatment Chart Review was conducted to identify any drug-related issues. The rPATD questionnaire was administered to both patients and their caregivers, particularly for those aged 60 and over to determine their attitude towards polypharmacy and deprescribing. The study involved 250 participants, consisting of 156 patients and 94 caregivers. Among the patients, 81 (51.9%) exhibited a negative attitude toward deprescribing, while 53 (56.4%) of the caretakers expressed a positive attitude. The Chi square test had shown significant association between participant characteristics (age and education) and their involvement in medication use. Treatment Chart Review was done in 108 inpatients and 53(49%) medication errors were found. These errors were communicated to the physicians. This study underscores that improving patient education and engagement can enhance treatment outcomes and reduce the medication burden. It also illustrates patients' and caregivers' readiness to participate in deprescribing practices with proper guidance from healthcare providers. However, the insufficiency of medical facilities in public hospitals has notably hindered the delivery of healthcare services.